Diblock copolypeptoids: a review of phase separation, crystallization, self-assembly and biological applications. Issue 25 (15th May 2020) - Xuan, Sunting; Zuckermann, Ronald N.
Abstract : Diblock copolypeptoids have the capacity to phase separate, crystallize, and self-assemble into a variety of nanostructures, which have shown great potential in a variety of biological applications. Abstract : Polypeptoids are biocompatible, synthetically accessible, chemically and enzymatically stable, chemically diverse, and structurally controllable. As a bioinspired and biomimetic material, it has attracted considerable attention due to its great potential in biological applications including drug and gene delivery, sensing, imaging, molecular recognition, and anti-cancer therapy. Diblock copolypeptoids have especially been of increasing interest in the materials chemistry community because of their capacity to microphase separate and self-assemble to form a variety of nanoarchitectures. This review will discuss recent studies on diblock copolypeptoids regarding their synthesis, microphase separation, crystallization, self-assembly, and biological applications.